Autotaxin facilitates selective LPA receptor signaling. Issue 1 (19th January 2023) - Salgado-Polo, Fernando; Borza, Razvan; Matsoukas, Minos-Timotheos; Marsais, Florence; Jagerschmidt, Catherine; Waeckel, Ludovic; Moolenaar, Wouter H.; Ford, Paul; Heckmann, Bertrand; Perrakis, Anastassis
Summary: Autotaxin (ATX; ENPP2) produces the lipid mediator lysophosphatidic acid (LPA) that signals through disparate EDG (LPA1–3 ) and P2Y (LPA4–6 ) G protein-coupled receptors. ATX/LPA promotes several (patho)physiological processes, including in pulmonary fibrosis, thus serving as an attractive drug target. However, it remains unclear if clinical outcome depends on how different types of ATX inhibitors modulate the ATX/LPA signaling axis. Here, we show that the ATX "tunnel" is crucial for conferring key aspects of ATX/LPA signaling and dictates cellular responses independent of ATX catalytic activity, with a preference for activation of P2Y LPA receptors. The efficacy of the ATX/LPA signaling responses are abrogated more efficiently by tunnel-binding inhibitors, such as ziritaxestat (GLPG1690), compared with inhibitors that exclusively target the active site, as shown in primary lung fibroblasts and a murine model of radiation-induced pulmonary fibrosis. Our results uncover a receptor-selective signaling mechanism for ATX, implying clinical benefit for tunnel-targeting ATX inhibitors. Graphical abstract: Highlights: ATX is a dual-function protein acting as an LPA-producing enzyme and LPA chaperone Structural integrity of the ATX tunnel is essential to mediate signaling functions ATX-bound LPA signals preferentially via P2Y-family LPA receptors Occupancy of the ATX tunnel is crucial for ziritaxestat to exert inhibition in vivo Abstract : Salgado-Polo et al. report that occupancy of the tunnel of the LPA-producing enzyme ATX regulates signaling outcome, through P2Y-type LPA receptors. Inhibiting this chaperone function of ATX by tunnel-binding inhibitors, such as ziritaxestat, correlates with drug efficacy in a mouse lung fibrosis model.